E3 ubiquitin ligase OsPIE3 destabilises the B‐lectin receptor‐like kinase PID2 to control blast disease resistance in rice. Issue 5 (15th December 2022) - Wang, Ke; Li, Shen; Chen, Longxin; Tian, Haoran; Chen, Cong; Fu, Yihan; Du, Haitao; Hu, Zheng; Li, Runting; Du, Yanxiu; Li, Junzhou; Zhao, Quanzhi; et al.
Summary: Previous studies have reported that PID2, which encodes a B‐lectin receptor‐like kinase, is a key gene in the resistance of rice to Magnaporthe oryzae strain ZB15. However, the PID2‐mediated downstream signalling events remain largely unknown. The U‐box E3 ubiquitin ligase Os PIE3 (PID2‐interacting E3) was isolated and confirmed to play key roles in PID2‐mediated rice blast resistance. Yeast two‐hybrid analysis showed that the armadillo repeat region of Os PIE3 is required for its interaction with PID2. Further investigation demonstrated that Os PIE3 can modify the subcellular localisation of PID2, thus promoting its nuclear recruitment from the plasma membrane for protein degradation in the ubiquitin–proteasome system. Site‐directed mutagenesis of a conserved cysteine site (C230S) within the U‐box domain of Os PIE3 reduces PID2 translocation and ubiquitination. Genetic analysis suggested that OsPIE3 loss‐of‐function mutants exhibited enhanced resistance to M. oryzae isolate ZB15, whereas mutants with overexpressed OsPIE3 exhibited reduced resistance. Furthermore, the OsPIE3 / PID2 ‐double mutant displayed a similar blast phenotype to that of the PID2 single mutant, suggesting that OsPIE3 is a negative regulator and functions along with PID2 in blast disease resistance. Our findings confirm that the E3 ubiquitin ligase Os PIE3 is necessary for PID2‐mediated rice blast disease resistance regulation.